Analysis of Mortality in Africanized Honey Bee Colonies with High Levels of Infestation by Varroa destructor - de Mattos, Igor Medici [UNESP]; Chaud-Netto, Jose [UNESP] (California State University, 2012)
The mite Varroa destructor (Anderson & Treuman 2000) is one of the world's most important plagues of apiculture. In Brazil this mite does not encounter good conditions for parasitism because weather conditions are not ideal for its maintenance, and some strains of Africanized honey bees are resistant to the parasite. This status is reflected in the low number of dead colonies caused by varroatosis and also the stability of infestation levels. The aim of this study was to evaluate the damage caused by mite infestations in hives with higher levels of infestation than the ones considered normal for Brazilian apiaries. The level of infestation in each colony was determined and the mortality rates of parasitized bees during development were periodically recorded. The G Test of Independence and a Test of Proportions were used to compare the data. The rates of mortality of pupae and larvae were mostly proportional to the level of infestation in each colony. All colonies showed mortality rates significantly higher than the control one. In Africanized honeybee colonies with high rates of infestation by Varroa destructor mortality rates varied from 19.27% to 23.28% in pupae ((X) over bar = 21.27%) and from 15.71% to 16.15% in larvae ((X) over bar = 15.93%), against 3.85% and 3.74% in the control colony, respectively. In the parasitized colonies the average rates of mortality caused by the hurtful effects of the mite were, respectively, 5.52 and 4.26 times greater in those two developmental stages. Thus it can be concluded that even in tropical regions, like Brazil, it is necessary to give special attention to the levels of mite infestation (IR), particularly where the IR tends to be higher.
Keywords: Africanized honeybees; Apis mellifera; Varroa destructor; mortality analysis; development